2008
DOI: 10.1128/aem.00517-08
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Class 1 Integron-Mediated Antibiotic Resistance Genes from Shiga Toxin-Producing Escherichia coli to a Susceptible E. coli K-12 Strain in Storm Water and Bovine Feces

Abstract: Transfer of class 1 integron-mediated antibiotic resistance genes has been demonstrated under laboratory conditions. However, there is no information concerning the transfer of these genes in an agricultural environment. The present study sought to determine if integron-mediated streptomycin and sulfisoxazole resistance genes could be transferred from Shiga toxin-producing Escherichia coli (STEC) strains 6-20 (O157: H7) and 7-63 (O111:H8) to the susceptible strain E. coli K-12 MG1655 in bovine feces (pH 5.5, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Ecological displacement of neighbouring genera, (b). Cell-to-cell signalling Simultaneously, the environmental organism has a resistance determinant (X r ) in its genome to be able to counteract any antimicrobial properties from its own inhibitory protein In a field study, conjugation and mobilization rates were increased more than 10-fold in the presence of pig manure Marcinek et al (1998) In studies by Hill et al (1992Hill et al ( , 1994, it was shown that large conjugative plasmids could be isolated, following conjugation with the indigenous population, in a P. putida recipient host containing a mobilizable nonconjugative plasmid van Veen et al (1997) Gotz and Smalla (1997) Marcinek et al (1998) Bale et al (1987) Hill et al (1992, 1994 Transfer of class 1 integronmediated antibiotic resistance genes from shiga toxin-producing Escherichia coli to a susceptible E. coli K-12 strain in storm water and bovine faeces Greater recovery of transconjugants in pH 7 storm water Antibiotic resistance genes in STEC could serve as a source of antibiotic resistance genes disseminated via conjugation to susceptible cells of other E. coli strains Nagachinta and Chen (2008) Today, the term 'antibiotic' is generally associated with the proactive treatment of bacteria infections of humans or animals. However, to have an understanding of antibiotic resistance in the clinical setting, it is important to appreciate the functions of antibiotics in the natural ecosystem and in environmental (nonanthropogenic) bacteria.…”
Section: Development Of Biofilm Entrapping Abr Bacteriamentioning
confidence: 97%
“…Ecological displacement of neighbouring genera, (b). Cell-to-cell signalling Simultaneously, the environmental organism has a resistance determinant (X r ) in its genome to be able to counteract any antimicrobial properties from its own inhibitory protein In a field study, conjugation and mobilization rates were increased more than 10-fold in the presence of pig manure Marcinek et al (1998) In studies by Hill et al (1992Hill et al ( , 1994, it was shown that large conjugative plasmids could be isolated, following conjugation with the indigenous population, in a P. putida recipient host containing a mobilizable nonconjugative plasmid van Veen et al (1997) Gotz and Smalla (1997) Marcinek et al (1998) Bale et al (1987) Hill et al (1992, 1994 Transfer of class 1 integronmediated antibiotic resistance genes from shiga toxin-producing Escherichia coli to a susceptible E. coli K-12 strain in storm water and bovine faeces Greater recovery of transconjugants in pH 7 storm water Antibiotic resistance genes in STEC could serve as a source of antibiotic resistance genes disseminated via conjugation to susceptible cells of other E. coli strains Nagachinta and Chen (2008) Today, the term 'antibiotic' is generally associated with the proactive treatment of bacteria infections of humans or animals. However, to have an understanding of antibiotic resistance in the clinical setting, it is important to appreciate the functions of antibiotics in the natural ecosystem and in environmental (nonanthropogenic) bacteria.…”
Section: Development Of Biofilm Entrapping Abr Bacteriamentioning
confidence: 97%
“…Plasmids in STEC often harbour antibiotic resistance gene cassettes on integrons (Colello et al, 2015;Singh et al, 2005;Van Meervenne et al, 2013;Zhao et al, 2001), and integron-positive strains have been found to be significantly more resistant to antibiotics compared to integron-negative strains (Van Meervenne et al, 2013). These integron-associated AR genes, such as aadA (aminoglycoside resistance), drfA1/dfrXII (trimethoprim resistance), sul1/sat1 (sulphonamides) and bla (against β-lactamase), can be transferred to other bacteria via plasmid conjugation (Cergole-Novella, Pignatari, Castanheira, & Guth, 2011;Kruger et al, 2015;Li, Wang, & Li, 2011;Maidhof et al, 2002;Nagachinta & Chen, 2008;Zhao et al, 2001). Class 1 integrons that contain a higher number of resistance gene cassettes than Class 2 integrons and confer better conjugation efficiency in bacteria harbouring them are found more often in STEC, as in other Gram-negative bacteria (Ahmed & Shimamoto, 2015;Colello et al, 2015;Gillings et al, 2008;Nagachinta & Chen, 2009;Vali et al, 2007).…”
Section: Acqu Is Iti On and Tr An S Miss I On Of Antib I Oti C Re Smentioning
confidence: 99%
“…Selection for antibiotic resistance has fixed lineages carrying diverse resistance determinants on a similarly diverse array of mobile elements. Such complex mobile elements now occur at high frequency in human-dominated systems, and in more natural ecosystems, where they can move by LGT into environmental organisms (Chee-Sanford et al, 2001; Nagachinta and Chen, 2008; Schlüter et al, 2008; Gillings et al, 2009a; Pellegrini et al, 2009). …”
Section: Evolutionary Consequences Of the Antibiotic Agementioning
confidence: 99%